CRISPR/Cas9-based QF2 knock-in at the tyrosine hydroxylase (th) locus reveals novel th-expressing neuron populations in the zebrafish mid- and hindbrain - Altbürger, Christian; Holzhauser, Jens; Driever, Wolfgang (Frontiers in Neuroanatomy, 2023)
Catecholaminergic neuron clusters are among the most conserved neuromodulatory systems in vertebrates, yet some clusters show significant evolutionary dynamics. Because of their disease relevance, a special focus has been on mammalian midbrain dopaminergic systems, which have important functions in motor control, reward, motivation and cognitive function. In contrast, in teleosts, it has been considered that the midbrain dopaminergic neurons have been secondarily lost. Here, we generated a CRISPR/Cas9-based knock-in transgene at the th locus, which allows the expression of the transcription factor QF2 of the Q-system linked to the Tyrosine hydroxylase open reading frame by an E2A peptide. The QF2 knock-in allele still expresses Tyrosine hydroxylase in catecholaminergic neurons. Coexpression analysis of QF2 driven expression of QUAS fluorescent reporter transgenes and of th mRNA and Th protein revealed that essentially all reporter expressing cells also express Th/th. We also observed a small group of previously unidentified cells expressing the reporter gene in the midbrain, and a larger group close to the midbrain-hindbrain-boundary. However, we detected no expression of the catecholaminergic markers ddc, slc6a3 or dbh in these neurons, suggesting that they are not actively transmitting catecholamines. The identified neurons in the midbrain are located in a GABAergic territory. Coexpression analysis with anatomical markers revealed the Th expressing neurons in the midbrain to be located in the tegmentum, and those close to the midbrain-hindbrain-boundary to be located in the hindbrain. Our data suggest that zebrafish may still have some evolutionary remnants of midbrain dopaminergic neurons.